Population characterization of the spiny lobster Panulirus Laevicauda (Latreille) off Northeastern and Southeastern Brazil - Ivo, Carlos Tassito Corrêa (Arquivos de Ciências do Mar, 2017)
The data which support the present paper were collected along the year 1994 in three fishing subareas along the coast of Ceará, Rio Grande do Norte, Espírito Santo and Bahia states. For analyses, the data collected in Espírito Santo and Bahia states coast were put together. A total of 978 spiny lobster, Panulirus laevicauda (Latreille) were sampled (Ceará State coast = 531 individuals, Rio Grande do Norte State coast = 338 individuals and Espírito Santo/Bahia States coast = 109 individuals). Measures of central tendency and dispersion were estimated for length, weight (total, carapace and abdomen) and width (total and carapace) for individuals caught in each subarea. Regression coefficients (slope and intersection) were also estimated for the following relationships: carapace length/length measures (total, abdomen, carapace width and abdomen width) and weight (carapace, total and abdomen)/carapace length. The data on this paper suggest that lobsters caught on fishing areas off Ceará and Rio Grande do Norte states belong to the same population group, but that lobsters caught on fishing areas off Bahia/Espírito Santo states belong to different population groups.